THU0306 Safety, Tolerability, Pharmacokinetics, and Pharmacodynamics of The BCL-2 Inhibitor Venetoclax (ABT-199) in A Phase 1 Single and Multiple Ascending Dose Study in Female Patients with Systemic Lupus Erythematosus. (15th July 2016) - Lu, P.; Fleischmann, R.; Curtis, C.; Ignatenko, S.; Desai, M.; Wong, S.L.; Grebe, K.M.; Zeng, J.; Medema, J.; Stolzenbach, J.
Abstract : Background: Apoptosis eliminates auto-reactive T and B cells during immune responses; failure of elimination is important in development of systemic lupus erythematosus (SLE). Elevated Bcl-2 expression may contribute to cell death abnormalities for auto-reactive cells. Venetoclax (ABT-199) is a selective, small-molecule Bcl-2 inhibitor. Objectives: To examine safety, tolerability, pharmacokinetics, and pharmacodynamics (PD) of venetoclax in female patients (pts) with SLE Methods: This was a single and multiple ascending dose (MAD), double-blind, randomized, placebo (PBO)-controlled, phase 1 study (NCT01686555 ) in women aged 18–65 y with SLE for >6 mo, receiving stable SLE therapy. Twelve cohorts were planned (N=96); in each cohort, 6 pts received venetoclax and 2 received PBO. Pts in cohorts 1–6 received single doses of venetoclax 10, 30, 90, 180, 300, and 500 mg, respectively, or matching PBO. Pts in MAD arms (cohorts 7–12) received 2 cycles (once daily for 1 wk, then 3 wk off in each cycle) of venetoclax 30, 60, 120, 240, 400, and 600 mg, or matching PBO, beginning after safety evaluation of the single-dose venetoclax 90-mg cohort. Results: In 98 enrolled pts, adverse events (AEs) were reported for 62% of pts receiving venetoclax and 48% receiving PBO; common AEs were headache (23% vs 24%, respectively) and gastrointestinal disorders (diarrhea [8% vs 4%], nausea [16% vs 12%], vomiting [8% vs 4%]). Most drug-related AEs were mild to moderate; no serious AE was reported with venetoclax. There were no deaths and no clinically relevant abnormalities of vital signs or electrocardiograms. Exposure to venetoclax was dose proportional, with a half-life of ∼7–17 h after single doses. PD effects of Bcl-2 inhibition included dose-dependent reductions of total lymphocytes and B cells (Figure ) after single and multiple venetoclax doses up to 600 mg. B cells were most sensitive to Bcl-2 inhibition, with up to 80% reduction from baseline in high-dose groups. Similar sensitivity was observed across B cell subsets. Total lymphocytes and T cells showed modest reduction; recovery of total lymphocytes occurred during the dosing interval of cyclic multiple dose regimens (Figure ). Levels of neutrophils, platelets, reticulocytes, hemoglobin, and safety laboratory values showed no consistent patterns or marked changes across single- and multiple-dosing groups. Conclusions: In female SLE pts, venetoclax was well tolerated in single and multiple doses; exposure appeared consistent with findings in cancer pts. PD assessments showed venetoclax-mediated reductions of lymphocytes and subsets. Acknowledgement: AbbVie funded the study; contributed to its design; and was involved in collection, analysis, and interpretation of the data and in writing, review, and approval of the abstract. All authors contributed to and maintained control over final content. Natalia Zhukovskaya, PhD, of Complete Publication Solutions, LLC, provided medical writing support. Disclosure of Interest: P. Lu Employee of: AbbVie, R. Fleischmann Grant/research support from: AbbVie, Consultant for: AbbVie, C. Curtis Grant/research support from: AbbVie, S. Ignatenko Grant/research support from: AbbVie, M. Desai Employee of: AbbVie, S. Wong Employee of: AbbVie, K. Grebe Employee of: AbbVie, J. Zeng Employee of: AbbVie, J. Medema Employee of: AbbVie, J. Stolzenbach Employee of: AbbVie